Cache Efficient Louvain with Local RCM - Gheibi, Sanaz; Banerjee, Tania; Ranka, Sanjay; Sahni, Sartaj (Proceedings - IEEE Symposium on Computers and Communications, 2020)
We develop a cache efficient Louvain community detection algorithm. Its effectiveness is demonstrated by bench-marking it against four existing Louvain algorithms on the Intel Knights Landing (KNL) and Haswell computational platforms using real and synthetic datasets. For a single iteration of Louvain, our algorithm obtains a speedup of up to 76.18% on real datasets on KNL, 51.91% on real networks on Haswell, 71.31% on synthetic networks on KNL, and 59.13% on synthetic networks on Haswell. These percentages using 2 iterations are 62.91%, 43.27%, 67.61%, and 54.43%, respectively.